ANALISIS PATRONASE POLITIK TERHADAP BIROKRATISASI PEMERINTAHAN DALAM PEMILIHAN KEPALA DAERAH KOTA PADANG - Winanti, Sherly Atha (Jurnal Dinamika Sosial Budaya, 2020)
Competition in a government organization that has a position always causes negative friction. The source of all this is due to the absence of bureaucrats' policies in carrying out professional, efficient, neutral and honest duties and responsibilities. Implementation in the bureaucratic system is not spared from the view of the public who know that people who occupy bureaucratic positions always serve the community and become an intermediary between political parties and the government. It has become commonplace for bureaucrats to always use a system of mutualism, as well as mutual relations without harming one party to the other. In giving positions from superiors (patrons) to subordinates (clients), it is always included with a high desire and marukh that someone who has a high position then he must also balance with a broad and high power as well. Therefore the recruitment of bureaucratic members in the government does not always look at the functional side of a person, but because of the support of his subordinates. There must be a term that is always fixed in the mind and mind of a high-ranking bureaucratic official, that the stronger a person's power is always marked by the number of subordinates or staff he has especially in the city of Padang. The method used in this article is the writing method with literacy studies sourced from written sources, in the form of journals, articles, magazines, internet, literature or documents that are relevant to the problem under study. The results of the study with this literature study method are to analyze the relationship between patrons and clients towards government bureaucratization with the dimensions of parkinsonism or classic disease that cannot be overcome or eliminated which will have an impact on the wider community.
Keywords: Patronage; Government Bureaucracy; Parkinson's Bureaucracy